The Comprehensive Systematic Review of Low Back Pain and its Association with Physical Activity Levels - Maulida Hayati; Kus Ageriyawan (International Medical Journal Corp. Ltd, 2026)
Introduction: Low back pain (LBP) is a leading cause of disability worldwide. While physical activity (PA) is a cornerstone of LBP management, the precise nature of the dose-response relationship remains debated, with studies reporting protective, harmful, and null effects. This comprehensive systematic review synthesizes evidence from observational studies to clarify the association between PA levels and LBP, exploring how this relationship is modified by activity domain, intensity, population characteristics, and pain chronicity. Methods: A systematic review was conducted, screening studies based on pre-defined criteria: adult populations (≥18 years) with non-specific LBP; assessment of PA as a primary exposure; and reporting of LBP outcomes (e.g., incidence, severity, disability). Eligible designs included observational studies (cross-sectional, cohort, case-control), systematic reviews, and meta-analyses that used validated measurement tools. Data were extracted on study characteristics, PA and LBP assessment methods, primary association results, moderating factors, and study quality. Results: Eighty studies were included, comprising 56 cross-sectional and 16 prospective cohort designs, with sample sizes ranging from 30 to 365,307 participants. The findings reveal a context-dependent relationship. Moderate-to-vigorous leisure-time PA was consistently associated with a protective effect against chronic LBP (RR range 0.84-0.90) (1,2). Optimal doses were identified at approximately 400-670 minutes of MVPA per week or 1800-2400 MET-min/week (3,4). In contrast, occupational PA (18,20), heavy domestic labor (17), and sedentary behavior (9,12,23) were associated with increased LBP risk. The relationship was often U-shaped, with both very low and very high activity levels conferring greater risk (1,4,10,25). Protective effects were more pronounced in older adults (≥50 years) (10,11), women (12,13), and obese individuals (14-16). Physical activity was more strongly associated with reduced disability (33,36) and the prevention of chronicity (2,6) than with acute pain episodes. Discussion: The heterogeneity in findings is explained not by contradiction but by the context-specificity of the PA-LBP relationship. The domain of activity (leisure vs. occupation) and its intensity are critical determinants of effect. While moderate leisure activity is protective, obligatory and high-intensity occupational demands can be harmful. PA's benefits appear to accumulate over time, primarily preventing the transition to chronic pain and reducing disability rather than eliminating acute episodes. The association is further modified by individual factors like age, sex, and BMI, and is mediated by psychological factors such as fear-avoidance beliefs. Conclusion: This review concludes that the relationship between physical activity and low back pain is non-linear and highly context-dependent. Recommendations should promote moderate-to-vigorous leisure-time physical activity for the prevention and management of chronic LBP, particularly in at-risk populations. However, they must be personalized, considering an individual's age, occupation, BMI, and psychological state. Future research should prioritize the use of objective activity measures and longitudinal designs to further delineate causal pathways and domain-specific dose-response relationships.